IL‐1β Induces p62/SQSTM1 and Represses Androgen Receptor Expression in Prostate Cancer Cells. Issue 12 (15th October 2014) - Chang, M.A.; Patel, V.; Gwede, M.; Morgado, M.; Tomasevich, K.; Fong, E.L.; Farach‐Carson, M.C.; Delk, Nikki A.
ABSTRACT Chronic inflammation is associated with advanced prostate cancer (PCa), although the mechanisms governing inflammation‐mediated PCa progression are not fully understood. PCa progresses to an androgen independent phenotype that is incurable. We previously showed that androgen independent, androgen receptor negative (AR−) PCa cell lines have high p62/SQSTM1 levels required for cell survival. We also showed that factors in the HS‐5 bone marrow stromal cell (BMSC) conditioned medium can upregulate p62 in AR+ PCa cell lines, leading us to investigate AR expression under those growth conditions. In this paper, mRNA, protein, and subcellular analyses reveal that HS‐5 BMSC conditioned medium represses AR mRNA, protein, and nuclear accumulation in the C4‐2 PCa cell line. Using published gene expression data, we identify the inflammatory cytokine, IL‐1β, as a candidate BMSC paracrine factor to regulate AR expression and find that IL‐1β is sufficient to both repress AR and upregulate p62 in multiple PCa cell lines. Immunostaining demonstrates that, while the C4‐2 population shows a primarily homogeneous response to factors in HS‐5 BMSC conditioned medium, IL‐1β elicits a strikingly heterogeneous response; suggesting that there are other regulatory factors in the conditioned medium. Finally, while we observe concomitant AR loss and p62 upregulation in IL‐1β‐treated C4‐2 cells, silencing of AR or p62 suggests that IL‐1β regulates their protein accumulation through independent pathways. Taken together, these in vitro results suggest that IL‐1β can drive PCa progression in an inflammatory microenvironment through AR repression and p62 induction to promote the development and survival of androgen independent PCa. J. Cell. Biochem. 115: 2188–2197, 2014. © 2014 Wiley Periodicals, Inc.